Aster-B coordinates with Arf1 to regulate mitochondrial cholesterol transport - John-Paul Andersen; Jun Zhang; Haoran Sun; Xuyun Liu; Jiankang Liu; Jia Nie; Yuguang Shi (Elsevier, 2020)
Objective: Cholesterol plays a pivotal role in mitochondrial steroidogenesis, membrane structure, and respiration. Mitochondrial membranes are intrinsically low in cholesterol content and therefore must be replenished with cholesterol from other subcellular membranes. However, the molecular mechanisms underlying mitochondrial cholesterol transport remains poorly understood. The Aster-B gene encodes a cholesterol binding protein recently implicated in cholesterol trafficking from the plasma membrane to the endoplasmic reticulum (ER). In this study, we investigated the function and underlying mechanism of Aster-B in mediating mitochondrial cholesterol transport. Methods: CRISPR/Cas9 gene editing was carried out to generate cell lines deficient in Aster-B expression. The effect of Aster-B deficiency on mitochondrial cholesterol transport was examined by both confocal imaging analysis and biochemical assays. Deletion mutational analysis was also carried out to identify the function of a putative mitochondrial targeting sequence (MTS) at the N-terminus of Aster-B for its role in targeting Aster-B to mitochondria and in mediating mitochondrial cholesterol trafficking. Results: Ablation of Aster-B impaired cholesterol transport from the ER to mitochondria, leading to a significant decrease in mitochondrial cholesterol content. Aster-B is also required for mitochondrial transport of fatty acids derived from hydrolysis of cholesterol esters. A putative MTS at the N-terminus of Aster-B mediates the mitochondrial cholesterol uptake. Deletion of the MTS or ablation of Arf1 GTPase which is required for mitochondrial translocation of ER proteins prevented mitochondrial cholesterol transport, leading to mitochondrial dysfunction. Conclusions: We identified Aster-B as a key regulator of cholesterol transport from the ER to mitochondria. Aster-B also coordinates mitochondrial cholesterol trafficking with uptake of fatty acids derived from cholesterol esters, implicating the Aster-B protein as a novel regulator of steroidogenesis.